Reflecting on the Rationale for the Movement to Reclaim Educational Authority in Modern China's Anti-Christian Campaign - HAN Yuexiang, (Journal of Research for Christianity in China (JRCC), 2025)
In the 1920s, a profoundly influential anti-Christian movement and campaign to reclaim educational sovereignty swept across China. From today's perspective, this movement appears counterintuitive. Why, then, did so many people participate in or support it at the time? Could their rationale withstand scrutiny and critical examination? Regrettably, scholarly research approaching this question from this angle remains relatively scarce. Political correctness, nationalist thinking, and scientism served as the indisputable legitimacy of this movement. Yet, the flaws and omissions in these theoretical foundations were deliberately or inadvertently overlooked and sidestepped within the discourse of radical ideology. Without dissecting this historical event and phenomenon from the depths of intellectual history, a similar fate may prove difficult to avoid.